LEADERSHIP IN GOOD CORPORATE GOVERNANCE (GCG) AS A ROLE MODEL OF ANTI-FRAUD CULTURE - Mustika Prabaningrum Kusumawati (Association of Certified Fraud Examiners Indonesia Chapter, 2020)
The presence of Good Corporate Governance (GCG) in Indonesia is one of the solutions in creating activities that can help to avoid any form of scandal in the company including fraud. However, the reality of Good Corporate Governance (GCG) to date has not been fully implemented. The rules of Good Corporate Governance (GCG) itself can not necessarily be applied well by the parties in the company. It takes a leadership and maximal support from regulators in the form of legal umbrella that is expected to create an anti fraud culture in the implementation of Good Corporate Governance (GCG). In order to succeed, an organization requires a strong leader. The success and the failure of an organization are determined by its leader. It takes a leader who is able to carry out collaboration, inspire and motivate subordinates he leads because leadership is the main factor of the success or even the failure of an organization. In addition, a positive leadership type will also form a positive culture in a company that will eventually become a role model of anti fraud culture.